Clinical RNA sequencing confirms compound heterozygous intronic variants in RYR1 in a patient with congenital myopathy, respiratory failure, neonatal brain hemorrhage, and d‐transposition of the great arteries. Issue 10 (16th September 2021) - Shillington, Amelle; Zea Vera, Alonso; Perry, Tanya; Hopkin, Robert; Thomas, Cameron; Cooper, David; Suhrie, Kristen
Abstract: Background: Defects in the RYR1 ( OMIM#180901) gene lead to Ryanodine receptor type 1‐related myopathies (RYR1‐RM); the most common subgroup of congenital myopathies. Methods: Congenital myopathy presents a diagnostic challenge due to the need for multiple testing modalities to identify the many different genetic etiologies. In this case, the patient remained undiagnosed after whole‐exome sequencing (WES), chromosomal microarray, methylation analysis, targeted deletion and duplication studies, and targeted repeat expansion studies. Clinical whole‐genome sequencing (WGS) was then pursued as part of a research study to identify a diagnosis. Results: WGS identified compound heterozygous RYR1 intronic variants, RNA sequencing confirmed both variants to be pathogenic causing RYR1‐RM in a phenotype of severe congenital hypotonia with respiratory failure from birth, neonatal brain hemorrhage, and congenital heart disease involving transposition of the great arteries. Conclusion: While there is an ongoing debate about the clinical superiority of WGS versus WES for patients with a suspected genetic condition, this scenario highlights a weakness of WES as well as the added cost and delay in diagnosis timing with having WGS follow WES or even ending further genetic testing with a negative WES. While knowledge gaps still exist for many intronic variants, transcriptome analysis provides a way of validating the resulting dysfunction caused by these variants and thus allowing for appropriate pathogenicity classification. This is the second published case report of a patient with pathogenic intronic variants in RYR1‐RM, with clinical RNA testing confirming variant pathogenicity and therefore the diagnosis suggesting that for some patients careful analysis of a patient's genome and transcriptome are required for a complete genetic evaluation. The diagnostic odyssey experienced by this patient highlights the importance of early, rapid WGS.